Shifting the Mythic Discourse: Ambiguity and Destabilization in Joanne Kyger’s The Tapestry and the Web - Encarnación-Pinedo, Estíbaliz (Amaltea. Revista de Mitocrítica, 2020)
The Homeric Penelope, long hailed as a feminist icon just as much as an example of submissive wife, has been the focus of numerous revisions and interpretations ranging from the reactionary to the most subversive. This article analyzes Joanne Kyger’s revision of the mythic discourse in The Tapestry and the Web (1965) by studying two of the main strategies used by the poet: subtle shifts of focus and the use of alternative sources. Building from Joseph Campbell’s concept of the monomyth, which gave the poet the aesthetic freedom to move within Homer’s text, the article examines Kyger’s use of the mythic discourse to undermine the prevalence of patriarchal narratives and question their position as established categories. Operating inside and outside the Homeric construct, Kyger’s collection perpetuates and subverts the classical myth in a move that anticipates contemporary – feminist – revisions and adaptations.